The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/rssc.12341
|View full text |Cite
|
Sign up to set email alerts
|

An Instrumental Variable Procedure for Estimating Cox Models with Non-Proportional Hazards in the Presence Of Unmeasured Confounding

Abstract: Summary Two‐stage instrumental variable methods are commonly used for estimating average causal effects in the presence of an unmeasured confounder. In the context of the proportional hazard Cox regression models, this problem has recently received attention with several methods being proposed. Previously, we developed an improved estimator under the incumbent two‐stage residual inclusion procedure called ‘2SRI’ by adding a Gaussian frailty in the second stage. We now consider the more complex situation in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…We evaluated the behavior of the estimating equations we propose in (6) under two scenarios for the marginal timedependent hazard ratio; i) a three piece constant hazard ratio, and ii) a log linear time-dependent hazard ratio. In the first scenario, the estimation method is equivalent to applying the approach of MacKenzie et al [2] in early, middle and late follow-up settings, and that is how we implement and report the results.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated the behavior of the estimating equations we propose in (6) under two scenarios for the marginal timedependent hazard ratio; i) a three piece constant hazard ratio, and ii) a log linear time-dependent hazard ratio. In the first scenario, the estimation method is equivalent to applying the approach of MacKenzie et al [2] in early, middle and late follow-up settings, and that is how we implement and report the results.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…Because Wang et al's approach is designed for a binary instrument, we dichotomize the continuous instrument of our simulations at the median. Second, we have evaluated the performance of the estimator of Martínez-Camblor et al [6] which estimates the hazard ratios of a Cox model for the multivariable effect of the treatment and the omitted covariate; that is, it conditions on the omitted covariate.…”
Section: Comparatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the behavior of the estimating equations we propose in (6) under two scenarios for the marginal time-dependent hazard ratio; iq a three piece constant hazard ratio, and…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…[5] derived a consistent estimator for a structural Cox model. Martínez-Camblor et al [6] identified the role of frailties in estimation of the hazard ratio via the two-stage residual inclusion algorithm if the treatment and omitted covariate jointly satisfy a Cox model. In this paper we extend IV based estimation of the HR beyond proportionality of hazards.…”
Section: Introductionmentioning
confidence: 99%